M[EMOR]YTH - Clondir, Razvan (Design/Arts/Culture, 2023)
The visual experiment proposed by my portfolio is the result of current technologies integrated into the creative process. Using mobile devices, I capture static or video images, I record sounds. I can locate and set a multitude of technical parameters of the collected multimedia material; I can precisely locate the place where I take them. In the experiment, which I called “open work”, I used all the technology-mediated information to create an application that would infinitely assemble the digital material input in order to create collages or fragments of physical space through digital memory. Anyone can input the digital materials obtained in the same location in the application, each contribution is a personal vision of the place. This portfolio is one of the many artistic outcomes of the experiment.